Questões de gênero na organização da sociedade moçambicana : a mulher em xeque em "Niketche : uma história de poligamia" de Paulina Chiziane - Teixeira, Rejiane dos Santos (2018)
The novel Niketche: a history of polygamy, from Mozambican author Paulina Chiziane, introduces to the reader the reflections on what it means to be a woman of color in a patriarchal and post-colonized society. This book reveals the uncertainty and the sufferings of Mozambican women who fight for both their social and self-recognition by seeking their place in a society which is fragmented by the impositions of colonial oppresion and modernity. By introducing its female characters who are compelled to cope with Eurocentric patriarchy's violence, Niketche depicts both the past and present of those women and their obstacles on the search for empowerment. Therefore, this research has intended to raise discussions that theorize on the subjective and intersubjective relations of oppression, among the genders which are conferred to colonized women, besides weaving a review on the hegemonic feminist studies that do not consider the female idiosyncrasies and see gender as something separated from class and race, by treating the female category as universal and hiding from their guidelines the oppressions to which women of color are subjected. As a means of analyzing the effects of colonial imposition on Mozambique's social structure and on the life of its female citizens, one has utilized the gender studies of Mozambican sociologist Isabel Maria Casimiro and also researcher Signe Arnfred and theologian Irene Dias de Oliveira, who discuss the fractures that African tradition has suffered from colonization. The theoretical background that supports this research regarding its history before, while and after colonization comes from historians José Luís Cabaço and José Capela, besides contributions from Fr. Raúl Altuna on the Bantu culture – Mozambican predominant ethnicity. The discussions on the female and its break with tradition and empowerment in current Mozambican society were traced through the perspective of African theorists Ana Maria Loforte, Oyeronke OYEWÙMÍ, Marie Pauline Eboh, Conceição Osório and Teresa Cruz e Silva, who analyze the dominant relations which were established by gender in our current society. Contributions of essayist Inocencia Mata and Cameroonian philosopher Achille Mbembe's studies have also enriched the discussions on the theme.